Fezolinetant’s efficacy and safety in treatment of vasomotor symptoms in postmenopausal women: a meta-analysis and GRADE evaluation of randomized controlled trials - Abdallah R. Allam; Mohamed Salah Alhateem; Abdelrahman Mohamed Mahmoud (European Journal of Medical Research)
Abstract Background Postmenopausal women are more likely to experience vasomotor symptoms (VMS), such as heat sensation and sweating. Recent trials have investigated fezolinetant in the treatment of VMS in postmenopausal women. Our study aims to conduct a meta-analysis of these trials in order to estimate fezolinetant’s effectiveness and safety in the management of VMS in postmenopausal women. Method We searched Cochrane, PubMed, Scopus, and Web of Science for all published randomized controlled trials. Review Manager Software was used for the meta-analysis. The quality of evidence was graded using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) framework. Results Our study contained five trials with 3295 individuals with a mean age of 54.4 years. The frequency of VMS was significantly lower in the fezolinetant group compared to the placebo group [MD = − 2.42, 95% CI (− 2.81, − 2.04), P < 0.00001]. Additionally, when compared to the placebo group, the severity of VMS was significantly lower in the fezolinetant group [SMD = − 0.36, 95% CI (− 0.46, − 0.26), P < 0.00001]. Furthermore, there was no significant difference in the incidence of treatment-emergent adverse events (TEAEs) between the fezolinetant group and the placebo group [RR = 1.02, 95% CI (0.97, 1.07), P = 0.51]. Conclusion Fezolinetant is efficient and well-tolerated in the treatment of postmenopausal women with VMS.